Movement towards the adoption of non-traditional household lighting fuel energy in developing areas - Danlami, Abubakar Hamid; Applanaidu, Shri Dewi; Islam, Rabiul (Taylor & Francis, 2019)
Besides cooking, lighting is one of the most vital household energy needs. This study was conducted with the main aim of assessing the factors that influence household lighting fuel choice and consumption in developing areas. To achieve this objective, samples were selected using a cluster area sampling technique, whereby a total of 539 samples were utilised. The estimated multinomial logit model for the lighting fuel choice indicates that age of the household head, income level, urban location, number of rooms and the availability of electricity have positive impacts on the probability of electricity adoption. Therefore, a sound policy that ensures availability of cheap electricity to households will have a strong and wider impact on more households that will move towards the use of the modern lighting source. Additionally, raising incomes and campaign awareness will encourage households to shift away from the use of the traditional lighting source, which is full of pollution, towards a modern source of lighting.